Apoyo como pasante en la secretaría de planeación en la alcaldía de Santa Rosa De Viterbo (2023)
Located in the province of Tundama (Strategic Sciences Magazine, 2017) is Santa Rosa De Viterbo, a municipality recognized thanks to its history, culture and traditions, a place where country life still flourishes and is the main activity of the the majority of its inhabitants, this municipality has a mayor's office committed to development, the mayor's office has the Secretary of Planning and Infrastructure dedicated to improving the infrastructure, road network, and other factors in which the community can benefit, in the Secretary. There are qualified personnel and machinery for each of the projects to be carried out, the civil engineering intern entered during the final period of Mayor Wilson Báez mandate, where projects such as the footprint plate, network installation were found in execution. of sewerage, construction of the new market square, installation of the natural gas network, maintenance of the infrastructure of the rural education centers, and other works in the final stage of the mandate, the intern contributed to the Secretariat the knowledge acquired in degree, as well as advice, teamwork, leadership and good performance in each of the works in which he is involved, he is also assigned the task of maintaining the agency's machinery in optimal conditions where it is fulfilled and improves the condition of the machinery.